Chronic treatment with a tryptophan-rich protein hydrolysate improves emotional processing, mental energy levels and reaction time in middle-aged women - Mohajeri, M. H.; Wittwer, J.; Vargas, K.; Hogan, E.; Holmes, A.; Rogers, P. J.; Goralczyk, R.; Gibson, E. L. (British journal of nutrition, 2015)
Common pharmacological treatments of mood disorders aim to modulate serotonergic neurotransmission and enhance serotonin levels in the brain. Brain serotonin levels are dependent on the availability of its food-derived precursor essential amino acid tryptophan (Trp). We tested the hypothesis that delivery of Trp via food may serve as an alternative treatment, and examined the effects of a Trp-rich, bioavailable dietary supplement from egg protein hydrolysate on cognitive and emotional functions, mood state, and sleep quality. In a randomised, placebo-controlled, parallel trial, fifty-nine mentally and physically healthy women aged 45–65 years received placebo (n 30) or the supplement (n 29) (both as 0·5 g twice per d) for 19 d. Emotional processing was significantly changed by supplementation, exhibiting a shift in bias away from negative stimuli. The results for the Affective Go/No-Go Task exhibited a slowing of responses to negative words, suggesting reduced attention to negative emotional stimuli. The results for the Facial Emotional Expression Rating Task also supported a shift away from attention to negative emotions and a bias towards happiness. An increase in arousal-like symptoms, labelled ‘high energy’, shorter reaction times and a slight benefit to sustained attention were observed in the treated subjects. Finally, when the supplement was taken 60–90 min before bedtime, a feeling of happiness before going to bed was consistently reported. In summary, daily consumption of a low-dose supplement containing bioavailable Trp may have beneficial effects on emotional and cognitive functions.